Student podcasting for teaching-learning at university - Irene Acevedo de la Peña; Daniel Cassany (OmniaScience, 2024)
There is currently little research on the use of podcasting as a learning tool in the tertiary-level foreign language classroom. Here we attempt to partly fill that gap through a multiple case study of three university teachers who use this technology in their courses in Spanish as a foreign language. We obtained data for analysis primarily in two ways, through individual interviews with the teachers on two separate occasions and by compiling a corpus of all the podcasts (227 in total) the three teachers had used in their classes, most of them student-created. Given this last fact, our analysis focuses especially on the creation of podcasts by the students and the teacher's role in the process. Our findings show that podcasting as an educational tool can offer significant benefits for language learning. Student-produced podcasts, in particular, provide students with a context to practice their foreign language speaking skills but also reading and writing skills are also heavily engaged in the process of writing a script for what they will say in their podcast. The production of podcasts can also be highly motivating for students if the final product is posted online on an open-access host site; this means that native speakers of the target language could be among the potential listeners. On the downside, the process of having students produce podcasts requires considerable time and preparation on the part of both teachers and students, and students who are shy or less comfortable with technology may find the task challenging.